A WOLIO SCRIPTURE AS A SOURCE OF INSPIRATION IN THE CREATION OF ISLAMIC CALLIGRAPHY ART - Parta, I Wayan Seriyoga; Umar, Adam Almiftah; Hasmah (Institut Seni Indonesia Denpasar, 2024)
This research is based on developing the Wolio script into the creation of Islamic calligraphy paintings. The method applied uses a creation approach from Husein Hendriyana's theory regarding creating works (practice-led research). Through 4 stages of creation, starting with 1) Pre-design, containing preliminary research. 2) Designing and making designs/drawings using the Wolio script and the Buton Palace fort. 3) Embodiment, applying images into visual calligraphy, and 4) Appreciation exhibition. Data collection techniques were collected through observation, interviews, and documents (document study), then continued with a presentation of the creation process and the results achieved. This research suggests that Wolio script writing can be formulated into Islamic calligraphy. This creation resulted in 10 works using plaque technique painting as media with different themes/backgrounds, interpreting the Wolio script within the scope of the Buton palace as a primary source developed into artistic creations of Arabic script calligraphy. The final stage is that the works are exhibited to gain public appreciation. So that interaction and communication can be established, which inspires an increase in experience and knowledge, especially in artistic practice in Islamic calligraphy writing. Based on the evaluation results, this work is suitable as a reference for creative calligraphy. Seeing this potential, I recommend that the Cultural Heritage Development Agency coordinator in Kamali Baadia collaborate to create creative calligraphy using the Buri Wolio script.